Single leg lateral and horizontal loaded jump testing: reliability and correlation with long track sprint speed skating performance - Zukowski, M.; Herzog, W.; Jordan, M. J. (The Journal of Strength and Conditioning Research, 2023)
This study examined the intraday reliability of 2 novel unilateral loaded jump protocols designed for long track speed skaters. Highly trained (n = 26), national level athletes performed single leg jumps with a horizontal robotic resistance across 3 external load conditions (10 N, 7.5% of body mass and 15% of body mass) using their dominant limb. Jumps were performed in both the horizontal (JumpHorz) and lateral (JumpLat) direction to replicate the body position and line of force application observed during the running and gliding phases of on-ice acceleration. Subjects completed 2 consecutive trials of the same jump protocol to examine the intraday reliability of the peak velocity achieved for each loading condition. Peak velocity across each jump type and loading condition had good reliability (intraclass correlation coefficient >0.8, coefficient of variation <5%). Significant positive relationships (r = 0.5-0.8, p < 0.05; n = 22) were observed between all jump conditions and on-ice sprint race split times obtained including 100, 400, and 500 m. Our results indicate that unilateral loaded jump tests are reliable in speed skating athletes and may help practitioners diagnose and monitor lower-limb maximal muscle power capacity in a sport-specific manner.